2018
DOI: 10.1039/c8nj01614c
|View full text |Cite
|
Sign up to set email alerts
|

A novel 6-quinoxalinamine-based fluorescent probe for real-time detection of palladium(ii) ions in pure water and bio-imaging

Abstract: A novel fluorescent probe LK based on a quinoxalinamine derivative exhibited excellent selectivity toward Pd2+ and could be used for bio-imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 51 publications
0
6
0
1
Order By: Relevance
“…Further deallylation of 1 results in the formation of 2 (Scheme 1). Both compounds 1 and 2 were prepared in good yields and their structures were confirmed using 1 H, 13 C NMR, and elemental analysis (Supplementary Materials Figures S1-S4). In the 1 H NMR the singlet peak at δ 8.96 and 9.19 ppm corresponds to the formation of imine = C-H proton for compounds 1 and 2 respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further deallylation of 1 results in the formation of 2 (Scheme 1). Both compounds 1 and 2 were prepared in good yields and their structures were confirmed using 1 H, 13 C NMR, and elemental analysis (Supplementary Materials Figures S1-S4). In the 1 H NMR the singlet peak at δ 8.96 and 9.19 ppm corresponds to the formation of imine = C-H proton for compounds 1 and 2 respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The 1 H and 13 C NMR of 2 showed that it is formed by the deallylation of 1 with Pd 2+ which is confirmed by disappearance of the allyl peaks and the presence of the phenolic proton peak in 1 H NMR ( Figure S9). The fluorescein moiety has no absorption in the visible region and is weakly fluorescent in solution due to the preponderance of the ring-closed spirolactam structure, which is evident by 13 C NMR signals at δ 65.3 and δ 63.9 ppm for compounds 1 and 2, respectively [41,42]. The blue fluorescence in 1 arises due to the electron transfer (ET) from allyloxy benzene to the fluorescein ring.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quinoxaline and its derivatives are important benzopyrazine compounds with aromatic properties. Many functional quinoxaline derivatives are expected to be used as molecular probes, chemical switches and supramolecular receptors , and have practical applications in medical drugs, agricultural drugs, dyes, and other fields . Therefore, the synthesis and research of quinoxaline compounds have attracted much attention.…”
Section: Introductionmentioning
confidence: 99%
“…基于香豆素、罗丹明等多种结构用来检测 Pd 2+ 的荧光探针已被开发, 获得了较好的效果 [29][30][31][32][33][34][35][36][37][38] . 在已报 道的探针中, 多数是配位型荧光探针, 抗干扰性能略有 影响 [39][40][41][42][43][44][45][46][47][48][49][50] ; 少量是反应型荧光探针, 实现了对 Pd 2+ 的专 一性识别, 但是部分探针发射波长较短, 不能达到近红 外区域 [51][52][53][54][55][56][57] ; 而已报道的近红外探针又合成复杂、成本 较高, pH 适用范围较窄, 限制了这些探针的进一步应 用 [58][59] .…”
unclassified